2015
DOI: 10.1007/s10909-014-1264-8
|View full text |Cite
|
Sign up to set email alerts
|

Probing Phase Coherence Via Density of States for Strongly Correlated Excitons

Abstract: We present the calculation of the coherent spectral functions and density of states (DOS) for excitonic systems in the frame of the three-dimensional extended Falicov-Kimball model. Using gage-invariant U(1) transformation to the usual fermions, we represent the electron operator as a fermion attached to the U(1) phase-flux tube. The emergent bosonic gage field, related to the phase variables, is crucial for the Bose-Einstein condensation (BEC) of excitons. Employing the path-integral formalism, we manipulate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 58 publications
(113 reference statements)
2
41
0
4
Order By: Relevance
“…This scenario of the excitonic condensation at the zero interlayer coupling is converging well with the general discussion about coherent excitonic density of states in the semiconducting systems (see in Ref. [20]), where it has been shown that a large amount of states in the DOS (without the hybridization gap) is the sign of the coherent excitonic condensates in these systems.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This scenario of the excitonic condensation at the zero interlayer coupling is converging well with the general discussion about coherent excitonic density of states in the semiconducting systems (see in Ref. [20]), where it has been shown that a large amount of states in the DOS (without the hybridization gap) is the sign of the coherent excitonic condensates in these systems.…”
Section: Resultssupporting
confidence: 89%
“…More recently, it has been shown [19,20] that the single-particle coherent density of states (DOS) in the usual two-dimensional (2D) [19] and three-dimensional (3D) [20] semiconducting systems at the zero temperature limit is always finite, reflecting with the excitonic condensate regime in these systems. For the 3D semiconducting systems, the coherent DOS spectra survive also for the higher temperatures [20]. This situation is also typical for the double layer electronic structures at the half filling [21] when considering the electron-hole pair formation and condensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a series of recent theoretical works suggest the importance of the phase correlations on the phase transition scenario in the excitonic systems [18][19][20][21][22][23]. Particularly, in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the phase coherence in the excitonic pair plasma is discussed there, with a classification of two distinct phase transitions in the excitonic plasma and the discussion about the exciton BEC is provided. It is shown [18][19][20]22,23] that in the low density limit of the excitonic pairs, the critical temperature of excitonic BEC should be much smaller than the temperature of the pair formation.…”
Section: Introductionmentioning
confidence: 99%